Students’ Integrated Science Process Skills and Argumentation in Basic Natural Science Lecture - Asih, Findiyani Ernawati; Novita, Dian; Ardhana, Ivan Ashif (Jurnal Pendidikan dan Pengajaran, 2022)
The society 5.0  era requires the active contribution of the younger generation to solve problems in the community through implementation of scientific methods which involve integrated science process skills (i-SPS). The rapid technological development makes social science students able to practice i-SPS through practicum methods. In addition, the existence of internet access can facilitate them to criticize phenomena through argumentation.. The aim of this study was analyzing the integrated science process skills (i-SPS) and argumentation of social science students. i-SPS were trained through demonstration methods and virtual experiment methods using pHET simulations, while argumentation were trained through debate activities involving pro-groups (pseudoscience view) and contra groups (scientific view). The research design was mixed method, the qualitative aspect is a content analyzing on i-SPS achievement of social science students who did rotation learning methods, while the quantitative aspect was the correlation test between i-SPS by pHET and argumentation. Mean score of  i-SPS by pHET was 83.46 and i-SPS by Demonstration was 55, while mean score of argumentation waas 77.88. The results of the nonparametric correlation test was r calculation was 0.175 smaller than r table 0.404 (sig 0.05 and N 24), so it was concluded that no correlation between i-SPS by pHET and argumentation. Majority of social science students about 75% have unequal category combinations of i-SPS by pHET and argumentation. Students’ i-SPS-PHET does not affect their argumentation. Several factors can influence the argumentation of social students, such as experience about phenomena, information disclosure in digital era , and the characteristics of debate involves pro and contra groups which expands knowledge.